Cat's cradle - Vonnegut, Kurt (Dial Press Trade Paperbacks, 2010)
A young writer decides to interview the children of a scientist primarily responsible for the creation of the atomic bomb. This is an apocalyptic tale of the planet's ultimate fate, featuring a cast of unlikely heroes.